Período Seco Anterior e Período de Serviço sobre a Produção de Leite e Gordura na Raça Holandesa no Estado de Minas Gerais - De Oliveira, Antonio Ilson Gomes (1999)
To evaluate the effect of previous days dry (PDD) and days open (DO) on milk (M305) and fat (F305) yield in 305 days and milk (MDAY) and fat (FDAY) yield per day of calving interval in Holstein cows, a data set contained 5,454 lactations from the Minas Gerais Holstein Cattle Breeders Association were analyzed. The model included effects of: nucleus (5), heard-year: nucleus, genetic group (1- 31/32 Holstein, 2- upgraded Holstein with known genealogy and 3- pure of origin Holstein), season-calving age in classes, previous days dry (28 classes), days open (21 classes) and lactation length (linear effect). The means, standard error and coefficient of variation for M̂305, F305, MDAY and FDAY were 5,721.60(13.87 kg) -CV, 17.90%, 191.04(0.46 kg) - CV, 18.20%, 15.04(0.04 kg) - CV, 18.02% and .5041 (.0011kg) - CV, 17.66%, respectively. Higher DO were related to lower M305 and F 305 and MDAY and FDAY, described by equations M305 = 5,982.93 - 4.3042 DO (R2 = 85.15%) and M̂DAY = 19.4569 - 0.04289 DO (R2 = 98.87%). The relations among this traits with the means of PDD classes were described by cubic equations: M̂ 305 = 4,910.70 + 14.0799 PDD - 0.0877 PDD2 + 0.00016 PDD3 (R2 = 53.99%) and MDAY = 12.62 + 0.0396 PDD - 0.00025 PDD2 + 0.00000045 PDD3 (R2 = 56.58%). Significant effect of all the other factors in all the evaluated traits was observed. The adjustment, mainly for MDAY and FDAY for days open, may be important in the genetic evaluations.